2012
DOI: 10.1111/j.1399-5448.2012.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bolus and food calculatorDiabeticson glucose variability in children with type 1 diabetes treated with insulin pump: the results of RCT

Abstract: The use of the Diabetics software by patients educated at the WPTS is safe and reduces 2-h postprandial BGL's and glucose variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
1
21
0
2
Order By: Relevance
“…Siavash et al reported that a mobile phone‐based bolus advisor significantly decreased BGC by 38 mg/dL compared with the control group, in which the reduction was 16 mg/dL, but changes in HbA1c and number of hypoglycemic episodes did not different between the two groups. In another trial, Blazik and Pankowska showed in a 3‐month randomized trial that patients using a software bolus calculator had better results in terms of 2‐h postprandial BGCs, smaller mean BGC, smaller variations in BGC, and a higher percentage of BGC in the target range 70–180 mg/dL. Simultaneously, there were no differences in the number of hypoglycemic events or HbA1c concentration or insulin requirements.…”
Section: Discussionmentioning
confidence: 98%
“…Siavash et al reported that a mobile phone‐based bolus advisor significantly decreased BGC by 38 mg/dL compared with the control group, in which the reduction was 16 mg/dL, but changes in HbA1c and number of hypoglycemic episodes did not different between the two groups. In another trial, Blazik and Pankowska showed in a 3‐month randomized trial that patients using a software bolus calculator had better results in terms of 2‐h postprandial BGCs, smaller mean BGC, smaller variations in BGC, and a higher percentage of BGC in the target range 70–180 mg/dL. Simultaneously, there were no differences in the number of hypoglycemic events or HbA1c concentration or insulin requirements.…”
Section: Discussionmentioning
confidence: 98%
“…Carbohydrate quantification is traditionally recommended for prandial insulin dose estimation. However, there is growing evidence that other macronutrients should also be taken into account when determining the prandial insulin dose (1)(2)(3)(4)(5)(6)(7). In particular, high fat and high protein meals have been shown to increase postprandial glycaemia for at least 5 h (2,6,8).…”
Section: Introductionmentioning
confidence: 99%
“…Initial experience with BCs came from insulin pumps (continuous subcutaneous insulin infusion [CSII]) in both adult and pediatric–adolescent populations. We have also published short reports of our experience with BCs in CSII .…”
Section: Introductionmentioning
confidence: 99%